The H-Index, A Bibliometric Indicator With Several Limitations: Critical Reflections - Tarro, Giulio; De Giorgio, Giovanni (British Journal of Healthcare and Medical Research, 2025)
The h-index, proposed by Hirsch in 2005, is a useful bibliometric indicator for characterizing a researcher’s scientific output. Since its introduction, although its widespread adoption has been rapid, thanks in part to its relatively simple calculation, several authoritative scholars have highlighted the numerous limitations of this widespread and renowned index, which measures a researcher’s scientific impact by taking into account the number of publications and the number of citations those publications have received from other researchers. Therefore, in addition to taking productivity into account, the indicator also takes into account the researcher’s impact within the scientific community. Based on our study, we believe there are several limitations that could seriously compromise the usefulness of this well-known bibliometric indicator. The h-index is important, yes, but not exhaustive, and in the absence of other indicators, it could prove both mathematically precise and misleading.